Dampak Membaca Satu Buku Cerita Bergambar Setiap Hari terhadap Keterampilan Bahasa dan Pertumbuhan Karakter Anak - Harefa, Severlina Mulyawati; Mustapa, Noviana; Kurniati, Euis; Wardhani, Wahju Dyah Laksmi (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
This study aims to analyze the impact of daily habit of reading picture storybooks on the character formation and language development of young children. The research employs a qualitative method using the Systematic Literature Review (SLR) approach, analyzing 22 relevant articles. The study findings indicate that the habit of reading one picture storybook daily contributes positively to enriching vocabulary, enhancing communication skills, and shaping children's character through the moral and social values embedded in stories. Factors influencing the effectiveness of this habit include active interaction between parents and teachers in accompanying children during reading, consistent reading frequency, as well as family and school environments that support early literacy. Regular reading activities have been shown to support holistic child development, both in language and character aspects. Therefore, reading picture storybooks daily can be an effective strategy in early childhood education, as it not only enhances language skills but also builds positive and empathetic personalities in children. This research highlights the importance of the role of adults and the environment in fostering literacy habits.